RESEARCH OF COSTUMER SERVICE SATISFACTION IN PHARMACEUTICAL RETAIL BY SERVQUAL MODEL - Sonja Ćortoševa; Emilija Gavranska-Nečev (Journal of Engineering & Processing Management, 2016)
New challenges faced by the company at the beginning of the 21st century require new approaches to quality management. Customer perception of the products and service quality is considered one of the key determinants of business performance and for the survival of the organization in a competitive market, and therefore the necessity of continuous monitoring of customer satisfaction. The aim of this paper is to investigate the customer service satisfaction at the selected pharmacy chain of a private wholesaler by using SERVQUAL model. The internal consistency, validity and reliability of the SERVQUAL scale with the Cronbach's alfa values, and factor analysis were assessed. The results of the analysis of the gap scores between customers’ expectations and their perceptions about the service quality in pharmacies indicates that the costumers are generally satisfied of the quality service (overall mean gap was -0.32). The score of the perceived quality was highest for safety dimension, and the lowest for its reliability and responsibility dimension. The biggest gap score was registered by the tangibles dimension (the atmosphere in pharmacies, completeness of assortment and price), and the lowest gap scores by empathy dimension (to give special attention to every individual, equal treatment and understanding of the consumer’ specific needs and pharmacy business hours). Recommendations are presented for improving the service quality and increase consumer satisfaction.
Keywords: custom service satisfaction; retail pharmacy; SERVQUAL model; gap analysis